Death: clinical and forensic anthropological perspectives - Etty Indriati, Etty Indriati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
All biological living beings inevitably die, and the ways to die vary although in essence death is a manifestation of the absence of Oxygen in the brain. After death, biological remains undertake proteolysis and decomposition. The aim of this article is to discuss clinical death, cerebral or medicolegal death, social death, phases of cerebral death, and biological process after deathÃ¢â¬âwhich is important for forensic medicine and forensic anthropology. How long a person die, if the time elapsed is in minutes, hours, days and a week,-it is within the field of medical forensic and pathological forensic. If the time elapsed after death is in weeks, months, or years, it is within the field of forensic anthropology. The time elapsed from biological death to the examination of the death is called postmortem interval. Five case studies on postmortem interval are presented in this article. It can be concluded that knowledge of the biological process of death and the fate of biological remains after death are important for handling abnormal death both in forensic medicine and forensic anthropology.Key words: clinical death, cerebral death, postmortem interval, forensic medicine, forensic anthropology